Rhipicephalus Tick: A Contextual Review for Southeast Asia - Tan, Li Peng; Hamdan, Ruhil Hayati; Hassan, Basripuzi Nurul Hayyan; Reduan, Mohd Farhan Hanif; Okene, Ibrahim Abdul-Azeez; Loong, Shih Keng; Khoo, Jing Jing; Samsuddin, Ahmad Syazwan; Lee, Seng Hua (Pathogens (Basel), 2021)
Rhipicephalus species are distributed globally with a notifiable presence in Southeast Asia (SEA) within animal and human populations. The Rhipicephalus species are highly adaptive and have established successful coexistence within human dwellings and are known to be active all year round, predominantly in tropical and subtropical climates existing in SEA. In this review, the morphological characteristics, epidemiology, and epizootiology of Rhipicephalus tick species found in SEA are reviewed. There are six commonly reported Rhipicephalus ticks in the SEA region. Their interactions with their host species that range from cattle, sheep, and goats, through cats and dogs, to rodents and man are discussed in this article. Rhipicephalus-borne pathogens, including Anaplasma species, Ehrlichia species, Babesia species, and Theileria species, have been highlighted as are relevant to the region in review. Pathogens transmitted from Rhipicepahalus ticks to host animals are usually presented clinically with signs of anemia, jaundice, and other signs of hemolytic changes. Rhipicephalus ticks infestation also account for ectoparasitic nuisance in man and animals. These issues are discussed with specific interest to the SEA countries highlighting peculiarities of the region in the epidemiology of Rhipicephalus species and attendant pathogens therein. This paper also discusses the current general control strategies for ticks in SEA proffering measures required for increased documentation. The potential risks associated with rampant and improper acaricide use are highlighted. Furthermore, such practices lead to acaricide resistance among Rhipicephalus species are highlighted.